COMPARISON OF CLASSICAL AND MODERN INTERPRETATIONS IN THE INTERPRETATION OF THE QUR'AN - Kgs M. Choirul Muchlis; Mutawakkil Faqih; Pathur Rahman; Abdur Rahman Nor Afif Hamid; Nanang Lidwan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study examines the comparison between classical and modern exegetical approaches within the Qur’anic interpretive tradition. Classical tafsir is primarily rooted in authoritative narrations through tafsir bi al-ma’tsur and tafsir bi al-ra’yi, emphasizing chains of transmission, linguistic analysis, and the views of early Muslim scholars. In contrast, modern tafsir emerged in response to socio-political and intellectual changes in the 19th and 20th centuries, with figures such as Muhammad Abduh and Rashid Rida leading the movement. Modern exegetical approaches highlight contextual, thematic, and maqashid-based interpretations aimed at addressing contemporary societal challenges, including social issues, scientific developments, and humanistic concerns. This study concludes that the primary distinction between these approaches lies in their interpretive orientation: classical tafsir is textual and traditional, whereas modern tafsir is rational, dynamic, and attuned to the realities of modern life. Nevertheless, both approaches contribute significantly to the evolving epistemology of Qur’anic interpretation and collectively enrich the understanding of the Qur’an’s universal message.